Microbiologic Spectrum and Antibiotic Susceptibility Pattern among Patients with Urinary and Respiratory Tract Infection - Maryam Sotoudeh Anvari; Mohammad Naderan; Mohammad Ali Boroumand; Saeed Shoar; Robab Bakhshi; Morteza Naderan (International Journal of Microbiology)
Aim. To demonstrate the prevalence of isolated organisms in urinary/respiratory tract infections and their antibiotic susceptibilities in a tertiary care center. Methods and Material. Between January 2008 and January 2010, patients referring to the clinic of cardiology or those admitted to the cardiac wards were enrolled in this cross-sectional descriptive study. Urine and sputum sampling was done for all the patients and the specimens underwent microbiologic examination and, in case of isolation of microorganism, antibiotic disk diffusion test was performed. Results. Escherichia coli (E. coli) was the most prevalent isolated organism in-hospital and community-acquired UTIs and was highly resistant to cephalothin in all the samples followed by cotrimoxazole, and ceftriaxone. It revealed high sensitivity to imipenem, amikacin, and nitrofurantoin. Acinetobacter constituted the most prevalent organism isolated from respiratory secretions and represented the highest resistance to ceftriaxone and the greatest sensitivity to imipenem. Conclusions. E. coli and Acinetobacter remain the most common uropathogenic and respiratory organisms, respectively. However, their increasing resistance to wide-spectrum imipenem, meropenem, and vancomycin is a major concern.